Advances in Optimizing Screw-lype Machines - Berlik, Stefan; Fathi, Madjid; Holland, Alexander (2006 IEEE International Conference on Systems, Man and Cybernetics)
The aim of this work is to present recent advances in porting the directed covariance matrix adaptation-evolution strategy (DCMA-ES) from the test function environment to a real-world application. DCMA-ES is a CMA-ES variant enhanced by the powerful concept of directed mutation. So far, DCMA-ES has already proven to outperform the classical CMA-ES for several test functions. Hence, the target is now to benefit from the strength of this approach also in real-world scenarios, as for example in optimizing screw-type machines. The paper is organized as follows: first we outline the DCMA-ES and the functioning of the screw-type machine. Then the performance of DCMA-ES on some test functions is presented as motivation for the porting whose current status is discussed. In the final section, conclusions are provided and the future work is sketched.